Pregnancy Outcomes after Early Amniotomy among Class III Obese Gravidas Undergoing Induction of Labor - Pasko, Daniel N.; Miller, Kathryn M.; Jauk, Victoria C.; Subramaniam, Akila (American Journal of Perinatology, 2019)
Objective We sought to evaluate differences in pregnancy outcomes following early amniotomy in women with class III obesity (body mass index ≥40 kg/m2) undergoing induction of labor.Study Design This is a retrospective cohort study of women with class III obesity undergoing term induction of labor from January 2007 to February 2013. Early amniotomy was defined as artificial membrane rupture at less than 4 cm cervical dilation. The primary outcome was cesarean delivery. Secondary outcomes included length of labor, a maternal morbidity composite, and a neonatal morbidity composite. A subgroup analysis examined the effect of parity. Multivariable logistic regression was used to adjust for covariates.Results Of 285 women meeting inclusion criteria, 107 (37.5%) underwent early amniotomy and 178 (62.5%) underwent late amniotomy. Early amniotomy was associated with cesarean delivery after multivariable adjustments (adjusted odds ratio [aOR], 2.05; 95% confidence interval [CI], 1.21–3.47). There were no significant differences in length of labor or maternal and neonatal morbidity between groups. When stratified by parity, early amniotomy was associated with increased cesarean delivery (aOR, 3.10; 95% CI, 1.47–6.58) only in nulliparous women.Conclusion Early amniotomy among class III obese women, especially nulliparous women, undergoing labor induction may be associated with an increased risk of cesarean delivery.
Keywords: amniotomy; induction of labor; obesity; cesarean delivery